Amortization Requirements May Increase Household Debt : A Simple Example - Svensson, Lars (IMF Working Papers; Working Paper ;, 2016)
Debt amortization requirements have been suggested as a way to reduce household indebtedness. However, a closer look reveals that amortization requirements may create incentives for both borrowers and lenders to borrow and lend more rather than less. Suppose that a household plans to finance a given housing purchase through a preferred future mortgage path. If that mortgage path violates a new amortization requirement, the household can still achieve its preferred mortgage path, net after savings, by initially borrowing more, investing the excess borrowing in a savings account, and fulfilling the amortization requirement by withdrawals from the savings account over time. This is obvious, if the savings interest rate equals the mortgage rate, because then the excess borrowing is costless. But even if the savings interest rate is less than the debt interest rate, so that the excess borrowing is costly, there remains a strong incentive to initially borrow more than without an amortization requirement. Furthermore, under these circumstances, it is profitable and quite riskless for banks to let borrowers borrow more and invest the excess borrowing in a savings account in the bank, giving lenders an incentive to lend more, not less, than without amortization requirements. Thus, amortization requirements as a way of reducing household indebtedness may be counterproductive.